Pelaksanaan Proses Belajar Mengajar Bahasa Daerah Bugis Kelas X Jurusan DKV di SMK Negeri 1 Barru - Gusnawati Gusnawati; Johar Amir; Andi Fatimah Yunus (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. The purpose of this study was to describe (1) The learning design, (2) Iimplementation of learning, and (3) Learning outcomes in implementing the teaching and learning process of the Bugis regional language, this research is expected to provide theoretical and practical benefits. This research is qualitative research namely class observations carried out based on aspects that are directly observed in the implementation of the teaching and learning class. The subjects of this study were 56 students of class X DKV Department at SMK Negeri 1 Barru. Data collection techniques in research namely, observation, tests, and documentation. The results of this study indicate that the results of observations on the implementation of the teaching and learning process for the Bugis regional language for class X DKV students at SMK Negeri 1 Barru are well realized based on observations in class. This can be seen from the observations matched on the observation sheet with the implementation of teaching and learning directly, observations of student learning outcomes which can be seen by tests given by the teacher to students, most students are unable to read lontara writing. The results of the study showed that students were active and enthusiastic about learning the Bugis local language by doing a number of things that could encourage learning the Bugis language so as to bring positive changes. The conclusion in this study is that the implementation of the teaching and learning process for class X DKV students at SMK Negeri 1 Barru is categorized as good.Keywords: learning design, implementation, learning outcomes